Aktueller Stellenwert der Device-Therapie - Kuschyk, Jürgen; Rudic, Boris; Borggrefe, Martin; Akın, Ibrahim (Herz, 2017)
Sudden cardiac death and chronic heart failure are among the main contributors to persisting high mortality rates in Germany. In addition to removal of causal factors and guideline-conform pharmacological therapy, therapy with cardiac implantable electronic devices (CIED) is of undisputed importance. Subcutaneous defibrillators have the advantage that they do not have intracardiac electrodes but still have the same efficacy and safety. For patients with a wide QRS complex and reduced ejection fraction, cardiac resynchronization has led to a reduction of morbidity and mortality. For patients with a normal QRS complex, cardiac contractility modulation had been shown to improve the quality of life, exercise capacity and left ventricular function. As a procedure for autonomic modulation in patients with reduced cardiac strength, the data for baroreceptor stimulation are the most convincing.